The contribution of blog-based writing instruction to enhancing writing performance and writing motivation of Chinese EFL learners - Han, Shujun (Frontiers in Psychology, 2023)
As an attempt to shed more light on the utility of blogs in educational contexts, the current research set out to explore the effectiveness of blog-based writing instruction on the writing skill and writing motivation of Chinese English-as-a-Foreign Language (EFL) students. 49 Chinese EFL students from two intact classes in a language school were selected as the participants through convenience sampling. Then they were assigned to an experimental (26 students) and a control condition (23 students) randomly. The students of the experimental group utilized blogs for posting their writing assignments whereas the control group were taught traditionally with no use of blogs or other technology devices. The IELTS writing tasks and L2 writing motivation scale were used for the data collection as pre- and post-tests. The findings revealed that although both groups improved their writing skill and motivation, the participants of the blog group performed better than those in the control group, confirming that the blog-based teaching substantially enhanced the writing skill and writing motivation of the EFL students. These findings may have notable implications for EFL instructors.